Imaginary, space and racial discrimination - Waldman, Maurício (GEOUSP Espaço e Tempo (Online), 2003)
This text assigns the relations of space, even in concrete dimensions as if in his imaginary one, with racial discrimination, and also articulates both themes within the relations among societies and environment. More than localize the racism exclusively in a concrete social level, this essay seeks to evidence cartography and imaginary geography, understood as a matrix to revivification and/or re-conception of excluding spatial dynamism . In this context, the emerging of linear and progressive interpretation of social time, based on suppression o f space by time, an inference understood in this material as a modern specificity, is com prehended as the base to origin genuine racist forms. Therefore, the racism would be pertinent exclusively for the western civilized pattern and no other. The racial discrimination would result of a civilization that took of the space for time, articulated with other negation process and nature rhythm. Eventually, this text seeks clarify the consequences of racial prejudice and the reconstruction of differences, as these specificities in a Globalization context